Infection control bundles in intensive care: an international cross-sectional survey in low- and middle-income countries. Issue 3 (March 2019) - ,; Akhvlediani, T.; Akkoyunlu, Y.; Amela, D.L.; Aqel, A.; Bagırova, F.; Carevic, B.; Candevir-Ulu, A.; Cevahir, F.; Dijk, M.V.; Dobrevska, R.; Donlan, S.; et al.
Summary: Background: In low- and middle-income countries (LMICs), the burden of healthcare-associated infections (HCAIs) is not known due to a lack of national surveillance systems, standardized infection definitions, and paucity of infection prevention and control (IPC) organizations and legal infrastructure. Aim: To determine the status of IPC bundle practice and the most frequent interventional variables in LMICs. Methods: A questionnaire was emailed to Infectious Diseases International Research Initiative (ID-IRI) Group Members and dedicated IPC doctors working in LMICs to examine self-reported practices/policies regarding IPC bundles. Responding country incomes were classified by World Bank definitions into low, middle, and high. Comparison of LMIC results was then made to a control group of high-income countries (HICs). Findings: This survey reports practices from one low-income country (LIC), 16 middle-income countries (MICs) (13 European), compared to eight high-income countries (HICs). Eighteen (95%) MICs had an IPC committee in their hospital, 12 (63.2%) had an annual agreed programme and produced an HCAI report. Annual agreed programmes (87.5% vs 63.2%, respectively) and an annual HCAI report (75.0% vs 63.2%, respectively) were more common in HICs than MICs. All HICs had at least one invasive device-related surveillance programme. Seven (37%) MICs had no invasive device-related surveillance programme, six (32%) had no ventilator-associated pneumonia prevention bundles, seven (37%) had no catheter-associated urinary tract infection prevention bundles, and five (27%) had no central line-associated bloodstream infection prevention bundles. Conclusion: LMICs need to develop their own bundles with low-cost and high-level-of-evidence variables adapted to the limited resources, with further validation in reducing infection rates.